Analisis Dinamika Struktur Pasar Wisatawan Mancanegara dan Implikasinya terhadap Industri Pariwisata Bali - Ni Komang Mei Gandari; I Putu Yoga Laksana; Leni Anggraini Susanti (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the development and dynamics of the international tourist market structure in Bali using the Structure-Conduct-Performance (SCP) paradigm, identify the strategic themes adopted by tourism businesses in response to market changes, and examine the implications of these findings for the tourism industry. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews, observation, and documentation involving representatives from Conrad Bali, Madhava Property Management, and The Butcher Club Steak House. The data were analyzed through data reduction, data display, and conclusion drawing based on the Structure-Conduct-Performance (SCP) framework. The findings reveal that the structure of Bali's international tourism market has changed significantly, as reflected in shifts in tourist source markets, the growing prevalence of last-minute booking behavior, intensified competition resulting from the increasing number of tourism businesses, and lower market entry barriers driven by digitalization. These structural changes have encouraged tourism businesses to adopt four major strategic responses: the digitalization of marketing and distribution, product and tourism experience differentiation, strengthened digital branding and storytelling, and greater operational efficiency and flexibility. These strategies have enhanced firms' adaptability, customer loyalty, operational efficiency, and long-term business sustainability in an increasingly competitive market. The study also identifies a decoupling phenomenon, whereby the increase in international tourist arrivals has not been accompanied by a proportional increase in economic benefits for tourism businesses due to the growing number of market participants and intensified competition.